Nigerian veterinarians’ attitude and response to small animal pain management (2017)
Nigerian veterinarians’ attitude and responses to pain management predominantly in small animals were evaluated using a structured questionnaire. The questionnaires were administered to representatives of seventy small/large animal clinics and hospitals distributed across ten states of the country. The respondents possess the Doctor of Veterinary Medicine (DVM) (58.6%), Master of Veterinary Science MVSc (32.9%) degrees, fellowship diplomas (5.7%) and PhD (2.9%) degree. Majority of the respondents (92.9%) had less than 20 years of post DVM clinical experience. Seventy- nine percent (79%) had good understanding of animal pain perception while 43% still hold the misconception that some degree of pain is beneficial to an animal after surgery. Pain rating excellently assigned to fracture reduction by 83% of practitioners, but inappropriately assigned by 66% of practitioners to caesarean section, 66% to laparotomy, 63% to ovariohysterectomy, 60% to mastectomy and 60% to dental procedures. Xylazine, lignocaine and ketamine were anaesthetic/analgesics commonly used. Respondents (98%) recognized pain based on animal’s response to painful body part palpation, attitude of animal (97%), history by care giver (80%) and inappetence (73%). Determinants of analgesic drug choice for dogs/cats were: analgesic efficacy (99/29%); potential for toxicity (95/38%); availability (93/43%), side effect (86/42%), cost (82/37%), availability of information on the drug (76/36%), and ability of analgesic drug to cause sedation in the animal (65/33%). Respondents sourced information for analgesic therapeutics from: literature (73%), internet (80%), and drug leaflet (98%). In conclusion, most veterinarians surveyed had understanding of animal pain perception and use anaesthetic protocols that provide analgesia. Nonetheless, some of them still hold on to the misconception that minimal pain perception is beneficial to the patient at the post-operative period which may have influenced their non-provision of additional analgesia post-operatively